Pengaruh Problem Based Learning Perbantuan Permainan Tradisional Congklak Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - diana, nanang; rahhman, nur; adiansha, adi apriadi; putri; muslim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to test the influence of the Problem Based Learning (PBL) model assisted by traditional congklak games on the mathematics learning outcomes of grade II elementary school students. The background of this research departs from the low ability of students to solve addition and subtraction problems independently, which is caused by a learning approach that is still expository and does not actively involve students. Using a one group pretest-posttest design, this study involved 26 students at SDN 2 Bolo. The results showed an increase in the average score of students from 53.46 in the pretest to 85.38 in the posttest. With a mean average difference of 31.92 points. The t-test showed significant results (p < 0.000), which showed a significant difference between pretest and posttest scores that the coneckle-assisted PBL model was effective in improving students' mathematics learning outcomes. The integration between PBL and congklak games not only strengthens the understanding of mathematical concepts, but also encourages active participation, logical thinking, and motivation for students to learn in a fun and contextual way.